Quality Impact on Software Performance - Corrêa, Ulisses B.; Millani, Luís F. G.; Beck, Antônio C. S.; Carro, Luigi (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Nowadays, market needs pose novel challenges to computer science requiring increasingly computational capacity to deal with more and more complex applications. Embedded systems represent a large slice of these new complex systems. This scenario promoted the employment of advanced hardware platforms on embedded systems. However, embedded software development has not progressed at the same pace. Although high-level technologies have been employed in embedded development it still lacks of understanding about their impact on physical constraints, which are extremely important on embedded domain. This paper analyzes Object Oriented (OO) and procedural implementations running on different processor organizations. We demonstrate that for the future embedded processors the gains of the old-fashioned procedural code over OO code do not justifies the risks of delayed time-to-market.